Comparison of stent-related symptoms, passive ureter dilatation and stone clearance rate using 4.5 French versus 6 French double J stenting of unfavourable ureter: a prospective randomized controlled trial in a tertiary care centre - Nagabhairava, Manu K.; Javali, Tarun; T., Manasa; Puvvada, Sandeep; Patil, Amit; D., Ramesh (International Journal of Research in Medical Sciences, 2024)
Background: Retrograde intrarenal surgery (RIRS) is the standard of care for renal stones of less than 1.5 cm and less than 1000 Hounsfield units (HU). Most virgin ureters do not allow the flexible ureteroscope in the first setting. Placement of a D-J stent in the ureter dilates the ureter. Therefore, our study aimed to compare stone clearance rates and symptom complex of passive ureteral dilation following 4.5 French/Fr versus 6 French/Fr double J (DJ) stent placement. Methods: After obtaining ethics approval and written informed consent, 100 patients satisfying the inclusion and exclusion criteria were included and data recorded. patients were randomized into group A (4.5 Fr) and group B (6 Fr). Stent was placed. After 4 weeks, symptoms were assessed by the ureteral stent symptom questionnaire (USSQ). Following retrograde intrarenal surgery (RIRS) successful passage of ureteric access sheath (UAS) and stone clearance rates were assessed. Results: The surgical success rate, stone clearance rate was similar in the two groups (p value: more than 0.05). The USSQ score was significantly lower in group A (p value: 0.001). Conclusions: Stent of smaller diameter (4.5 Fr) is associated with less patient discomfort with similar surgical completion rates and stone clearance.